The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/maq.12208
|View full text |Cite
|
Sign up to set email alerts
|

Serenity: Violence, Inequality, and Recovery on the Edge of Mexico City

Abstract: Over the last decade, there has been a sharp increase in drug addiction in Mexico, especially among the urban poor. During the same period, unregulated residential treatment centers for addiction, known as anexos, have proliferated throughout the country. These centers are utilized and run by marginalized populations and are widely known to engage in physical violence. Based on long-term ethnographic research in Mexico City, this article describes why anexos emerged, how they work, and what their prevalence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 26 publications
0
76
0
Order By: Relevance
“…54,5658 This scale up of evidence-based biomedical and harm reduction interventions is occurring despite China’s previous investment in a compulsory treatment infrastructure; as such, tensions remain between voluntary, public health-oriented approaches and compulsory detainment, 59 as they do in settings that include both compulsory and voluntary approaches, such as Mexico. 60,61 This may result in suboptimal treatment outcomes given that ongoing interactions with law enforcement and the threat of detainment within compulsory drug detention centers may cause drug-dependent individuals to avoid harm reduction services or engage in risky drug-using behaviors out of a fear of being targeted by police, 59 as has been observed in a range of settings. 6266 We also note that this is likely the case in settings seeking to control the harms of non-opioid substance use disorders such as cocaine use disorder, given that available interventions that have been shown to be effective have been undertaken using voluntary treatment approaches.…”
Section: Resultsmentioning
confidence: 99%
“…54,5658 This scale up of evidence-based biomedical and harm reduction interventions is occurring despite China’s previous investment in a compulsory treatment infrastructure; as such, tensions remain between voluntary, public health-oriented approaches and compulsory detainment, 59 as they do in settings that include both compulsory and voluntary approaches, such as Mexico. 60,61 This may result in suboptimal treatment outcomes given that ongoing interactions with law enforcement and the threat of detainment within compulsory drug detention centers may cause drug-dependent individuals to avoid harm reduction services or engage in risky drug-using behaviors out of a fear of being targeted by police, 59 as has been observed in a range of settings. 6266 We also note that this is likely the case in settings seeking to control the harms of non-opioid substance use disorders such as cocaine use disorder, given that available interventions that have been shown to be effective have been undertaken using voluntary treatment approaches.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that these ethnic groups have developed their own recovery support systems within their communities and are simply not a part of the Sober Living Network. For example, anexos , mutual-help recovery programs that provide structured daily routines, peer support, and daily Spanish-language Alcoholics Anonymous (AA) meetings that incorporate cultural elements from AA in Mexico (Garcia, 2015) are known to operate in Los Angeles (A. Pagano, personal communication, February 16, 2016). The experiences of these minority groups in SLHs and potential barriers to opening SLHs in neighborhoods with high concentrations of these groups warrant further study.…”
Section: Discussionmentioning
confidence: 99%
“…While there are some studies of anexos in Mexico (Garcia, 2015; Marín-Navarrete, Eliosa-Hernández, Lozano-Verduzco, Turnbull, & Tena-Suck, 2013; Rosovsky, 2009), and of non-anexo AA modalities utilized by Latino migrants in the U.S. (Anderson & Garcia, 2015; Garcia, Anderson, & Humphreys, 2015; Gordon, 1981), the present study is the first multi-year ethnographic study of U.S.-based anexos.…”
Section: Introductionmentioning
confidence: 94%
“…A qualitative study of Mexican men’s experiences in anexos revealed accounts of forced internment, rape, beatings, being made to sit for hours with one’s hands extended, and being required to eat from the same bowl that functioned as a toilet (Lozano-Verduzco, Marín-Navarrete, Romero-Mendoza, & Tena-Suck, 2016). Another study of anexos in Mexico City reported punitive practices such as residents being made to kneel on bottle caps or hold heavy weights for hours; being deprived of sleep and food; being kicked, punched, and cut; and having cigarettes extinguished on their backs (García, 2015). In 2013, an anexo in Tijuana was accused of allowing sexual abuse of women residents (Betanzos, 2013).…”
Section: Introductionmentioning
confidence: 99%